Notas sobre la génesis del desligamiento funcional - Ribes-Iñesta, Emilio (Acta Comportamentalia, 2020)
Several observations are presented as theoretical notes on the genesis of functional detachment in the Animal Kingdom. These notes deal with the conditions that make possible functional detachment, as psychological behavior, based upon the characteristics of reactional systems, some of them exclusive of human beings. An examination is done of the relations between detachment and biological organization, differential reactional systems and functional detachment, detachment as a spatiotemporal reactional gradient, temporal and spatial extra-situational distantiation, and detachment and linguistic reactive/active patterns. Finally, some reflections are made on interactive functional transitions based on sensibility and locomotion to those involving only conventional objects and reactive/active patterns.